Heat treatment method and application of medium-carbon alloy steel and high-carbon alloy steel
BQT heat treatment method solves the problem of insufficient hardness and wear resistance of tool steel by forming a multiphase microstructure of bainite, tempered martensite and carbide, improves brittle fracture resistance and ductility, and reduces quenching deformation. Extends the life of the material.
Patent Information
- Application Number
- CN202380025233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-13
- Publication Date
- 2025-01-10
AI Technical Summary
When the existing heat treatment methods of tool steels improve hardness and wear resistance, they often lead to insufficient brittle fracture and ductility, and multi-step treatment may cause quenching cracks and internal stress deformation, limiting the service life of the material.
BQT heat treatment method is adopted, including austenitization, isothermal annealing to form bainite ferrite, cooling to the martensite transition temperature range, and one or more tempering to achieve carbide precipitation strengthening, forming bainite, The multiphase microstructure composed of tempering martensite, residual austenite and carbides inhibits the precipitation of cementite and enhances the brittle fracture resistance of the steel.
Improve the hardness, strength, wear resistance and fracture resistance of tool steel, while reducing quenching deformation, maintaining high temperature stability, extending the service life of the material, and controlling the final microstructure of the steel through reasonable tempering steps, improving mechanical properties.
Smart Images

Figure BDA0005024698880000101 
Figure BDA0005024698880000102 
Figure BDA0005024698880000111
Abstract
Description
[0001] The subject of the invention is a method for heat treatment of medium and high carbon alloy steels, the purpose of which is to produce a fragmented, multiphase microstructure consisting of tempered bainitic ferrite and martensite, separated by a stable layer of residual austenite and a layer of finely dispersed alloy carbide precipitates that cause secondary hardness. The microstructure may also contain primary carbides and / or secondary carbides. The use of the proposed heat treatment for tool steels makes it possible to achieve enhanced brittle fracture resistance, high hardness, ductility, high strength parameters and wear resistance.
[0002] To date, the commonly used heat treatment to impart the desired mechanical and functional parameters to tool steels is martensitic quenching combined with single or multiple tempering. This process consists in gradually heating the steel to the austenitizing temperature, keeping it at this temperature, and then cooling it usually in oil, fluidized bed or air. Therefore, depending on the grade of steel, the quenched steel undergoes tempering, i.e. high temperature annealing in the range of usually from 400°C to 600°C. The effect of tempering is to reduce martensitic embrittlement, microstress relaxation and carbide precipitation, which significantly contributes to the strengthening of the steel. In tool steels with a higher carbon content, the precipitation process leads to the instability of the retained austenite, which undergoes a martensitic transformation during cooling. In this case, it is necessary to carry out several tempering operations (runs) to eliminate the steel embrittlement associated with the presence of newly formed martensite and further reduce the fraction of retained austenite. As a result of this treatment, a microstructure is produced consisting of primary carbides not dissolved during austenitization, tempered martensite, secondary and tertiary carbides and a small amount of retained austenite (usually up to 10% by volume). Such a treatment is presented, for example, in patent PL101241 and, in combination with mechanical treatment, in patents PL116046, PL78487 and PL123120.
[0003] Toughened tool steels are characterized by high hardness, good wear resistance and retention of mechanical properties at high operating temperatures. However, the main disadvantage of this solution is the occurrence of deformation or quenching cracks due to the introduction of internal stresses into the structure by the martensitic transformation. In addition, the relatively low ductility and fracture resistance of such treated pieces significantly limit their service life.
[0004] In WO99 / 02747, a method for strengthening steel by exploiting the phenomenon of secondary and tertiary carbide precipitation is used to form the properties of a high-strength steel having the following chemical composition (in % by weight): 0.03%-0.12% C, 0.1%-0.5% Si, 0%-2.0% Cu, 0.5%-2.0% Ni, 0.03%-0.12% Nb, 0.03%-0.15% V, 0.2%-0.8% Mo, 0.3%-1.0% Cr, 0.03%-0.05% Ti, 0.01%-0.05% Al. In this steel, a microstructure comprising tempered martensite, granular bainite and finely dispersed carbides and carbonitrides is produced due to continuous cooling to a temperature above 400° C. and subsequent high tempering. A similar microstructure can be obtained by using the heat treatment described in application CN109207693A, which consists of a continuous cooling from austenitization to room temperature, followed by freezing or low / medium tempering in the temperature range of 150°C-550°C to eliminate the retained austenite, and high tempering, the parameters of which depend on the grade of the steel. This treatment method is intended for low alloy steels with a carbon content of less than 0.5% by weight and fractions of alloying additives in the form of the following (in %): Cr≤4%, Mo≤1.5%, V≤0.5%, Mn≤1.5%, and Ni, Si and traces of Nb, Ti, B, the total content of which does not exceed 5% by weight. On the other hand, EP2126150 discloses a cold working tool steel having a completely or at least partially martensitic and / or bainitic structure, which is strengthened by precipitation of primary carbides, secondary carbides and intermetallic phases. It is also produced by a heat treatment comprising quenching and one or more temperings under continuous cooling. The steel described is characterized by improved weldability, as well as high hardness, wear resistance and good impact strength. In these inventions, the aim is to eliminate as much retained austenite as possible, since retained austenite is regarded as an undesirable component of the microstructure, and partial bainite transformation is not used as a tool to break up the original austenite grains and control the content of phase components in the final microstructure.
[0005] From GB999866A a method for heat treatment of a high speed steel is known, which contains (in wt%): 0.55%-1.06% C, 3.5%-5.5% Cr, 5.0%-24.0% W, maximum 14.0% Co, 0.75%-6.00% V, maximum 8.00% Mo. The method described comprises four consecutive steps: (I) gradual austenitization, (II) partial bainitization by austempering at a temperature ±5°C with the shortest incubation period for the bainite transformation, for the time required to produce about 10% bainite by volume, (III) martensite quenching to -80°C or lower, (IV) subsequent high tempering at 550°C or more. The result of this treatment is a multiphase microstructure consisting of tempered bainite, martensite and secondary carbides. The multiphase microstructure is characterized by high hardness, high impact strength and high wear resistance. The heat treatment method proposed in GB999866A is specifically for high-speed steels that do not contain silicon or aluminum, which cause carbides to precipitate from bainitic ferrite during bainite transformation and lead to lower bainite and / or upper bainite, which are characterized by higher brittleness compared to carbide-free bainite. High-speed steel does not contain Si or Al, for example to avoid having austenite in the final microstructure. In the cited invention, cooling to -80°C is used to transform at least 95% of the remaining austenite into martensite. Additional reduction of the austenite content is achieved by using multiple temperings that cause carbide precipitation and instability of the remaining austenite.
[0006] CN111876569A discloses a heat treatment method in which, as described above, strengthening of steel is achieved by precipitation of secondary carbides, bainite transformation and significant fragmentation of the multiphase microstructure. However, in the presented process, the bainitizing step follows the martensite quenching and tempering operation, making it possible to eliminate the disadvantages of lower bainite tempering, thereby increasing the impact strength of H13 steel, 42CrMo steel, Cr12MoV steel while maintaining their very high hardness. In the cited invention, martensite quenching is used after austenitizing, so that the size of the martensite lath bundle (martensite packet) formed, especially in the initial stage of transformation, is only limited by the size of the original austenite grains. As a result, the possibility of martensite fragmentation and further improvement of the strength and fracture resistance of the steel is limited.
[0007] Descriptions of chemical compositions and methods for obtaining a multiphase microstructure comprising tempered bainite, martensite and carbides can also be found in patent applications CN111593258 and CN101724736A related to low carbon steels.
[0008] It is widely described in the cited literature that the bainitic microstructure consists of two phases: carbon-supersaturated ferrite and plates or laths of cementite precipitations. Depending on the temperature and duration of the bainitic transformation, which influence the kinetics of the diffusion process, cementite can precipitate inside the bainitic ferrite grains, at an angle of 60° to the lath / plate axis (bottom bainite) or at the boundaries of the laths (top bainite). The bainitic structure is obtained by continuous cooling or isothermal annealing in the bainite formation range. Compared with martensite, bainite is characterized by a lower strength. At the same time, due to the reduced microstress, the lower bainite shows much better ductility than martensite.
[0009] Therefore, as described in the prior art presented above, the result of introducing a certain fraction of bainite into the martensitic microstructure due to a multi-step heat treatment is an increase in the impact strength of the steel while maintaining the preferred strength parameters, high hardness and wear resistance. However, the presence of cementite precipitates in the bainite that can condense under high temperature annealing may be a factor determining the low resistance to brittle fracture of the steel. In order to make it possible to use bainite transformation as a steel strengthening mechanism and eliminate embrittlement, steels with carbide-free bainite structures have been developed. Studies have shown that the process of cementite precipitation can be significantly delayed in the case of appropriate contents of silicon and / or aluminum. As a result, a microstructure of plates or laths comprising bainitic ferrite separated by thin layers of stable residual austenite is produced. Preferred chemical compositions of steels and well-defined parameters of austempering, which result in a carbide-free bainite structure with nano-sized components, are disclosed in US8956470, EP2410070A1, WO2010013054A2, US20110126946A1, PL228168 and PL219414. However, these inventions are mainly limited to low alloy steels and medium alloy steels with carbon contents in the range of 0.4%-1.1% by weight, and the isothermal annealing process is carried out at a temperature slightly above Ms in the range of 190°C-300°C to complete the bainite transformation, and may take up to several weeks.
[0010] From patent PL234049, it is possible to obtain a microstructure comprising primary alloyed carbides in a matrix of carbide-free bainite and retained austenite in a tool steel having the following chemical composition (in % by weight): 0.6%-2.3% C; 0.4%-2.5% Mn; 0.5%-3.0% Si; at least one of the following carbide-forming elements: up to 17.0% Cr, up to 10.0% Mo, up to 4.0% V; and at least one alloying additive selected from the following group: up to 18.0% W, up to 0.2% Ti, up to 0.1% Nb, up to 2.0% Al, up to 4.5% Ni, up to 10.0% Co, up to 1.2% Cu, while satisfying: (%Cr+%Mo+%V)≥2.25% and (%Si+%Al)≥1.5%. As a result of austempering at a temperature above Ms but below 320° C., a bainitic structure with at least 50% by volume of nano-sized and / or submicron-sized particles is produced, while the retained austenite achieves thermal stability down to -40° C. In the cited invention, a binary microstructure of bainitic ferrite with retained austenite as a carbide matrix is sought. Neither martensitic transformation nor secondary hardness is used to increase the strength and hardness of the steel.
[0011] From PL234490 is known a heat treatment combining isothermal annealing with martensite quenching and partitioning (BQ&P). After the step of complete austenitization, the steel is subjected to isothermal quenching for the time required to obtain 10%-80% of bainitic ferrite by volume in the structure, and then the steel is cooled to a temperature between the martensite transformation start temperature (Ms) and the martensite transformation end temperature (Mf) of the retained austenite to finally undergo annealing to stabilize the retained austenite and reduce the martensite carbon supersaturation. The result of this heat treatment is a fragmented multiphase microstructure comprising carbide-free bainite, martensite and retained austenite, which leads to high hardness, high strength, good ductility and fracture resistance. Compared with simple isothermal quenching, this method effectively reduces the treatment time, but is limited to low-alloy steels or medium-alloy steels and steels with a silicon concentration and / or an aluminum concentration sufficient to suppress precipitation processes but not greater than (Si+Al)≤3.2%. In the cited invention, the purpose is to suppress any precipitation processes during the heat treatment step used. The partitioning temperature is chosen so that only diffusion redistribution of carbon from martensite to the remaining austenite occurs. The described method does not use precipitation strengthening to increase the hardness and strength of the steel. A similar treatment scheme is described in patent application CN102828011A, in which the partitioning step is replaced by tempering at a temperature above 300°C to increase ductility, fracture resistance and high cycle fatigue resistance while maintaining the high strength of the steel for the production of drilling tools. However, this treatment method is only used for low carbon steels with higher manganese and silicon contents.
[0012] The characteristics of steels for tool applications should be high hardness, wear resistance, good strength parameters and high temperature resistance during operation. However, it is also very important that they show increased brittle fracture resistance and relatively good ductility in order to extend the service life of cyclic and / or dynamic loading parts. The combination of these properties cannot be achieved by conventional heat treatment applications. It is known that the fraction and morphology of phase components are controlled by appropriate heat treatment design, allowing steel to reach the desired parameters. In conventional tool steels, in addition to strengthening by martensite and alloy carbide precipitation, the use of additional mechanisms strengthened by bainite transformation leads to a significant increase in ductility. However, the presence of cementite precipitates in the bainite structure can reduce the brittle fracture resistance of the material. Adding sufficient amounts of Si and / or Al makes it possible to suppress the precipitation process during austempering, resulting in an increase in the volume fraction of stable retained austenite in the final structure. From the research work [HKDHBhadeshia, Materials Science and Engineering, A481-482 (2008), 36-39], it seems that the appropriate austenite morphology to ensure its infiltration can significantly increase the plasticity, impact strength and fracture resistance of steel. However, this plastic phase should be in the form of narrow layers or finely dispersed grains, uniformly distributed in the structure, and its volume fraction should exceed 10%.
[0013] The object of the present invention is to produce steels with a nano-multiphase structure or a submicron multiphase structure providing a sufficient level of hardness and wear resistance while increasing ductility and fracture resistance. In addition, the developed heat treatment method for alloyed medium-carbon steels and high-carbon steels results in a reduction in quenching distortion compared to conventional martensitic quenching and tempering treatments while maintaining high temperature stability.
[0014] The subject of the invention is a method for heat treatment of medium and high carbon alloy steels undergoing bainite transformation, which is represented by the abbreviation BQT. The method comprising heating, cooling and tempering of the steel comprises the following consecutive steps:
[0015] In step (A), the steel is heated to the austenitizing temperature T A >A c1k And keep it at this temperature for a duration of t A .
[0016] In the next step (B), the bainite-transformed steel is cooled to an isothermal annealing temperature T B , where 350℃≥T B ≥MS(γ)+10℃ and keep at this temperature for a period of time t B , until 10%-70% volume fraction of bainitic ferrite is formed.
[0017] In step (Q), the steel is cooled to a temperature TQ , and keep it for a duration of t Q , until the temperature is equalized throughout the piece, the temperature T Q The martensitic transformation start temperature M of the retained austenite remaining after partial bainitization (step B) is s (γ r ) and the martensitic transformation end temperature M f (γ r )between;
[0018] In the final step (T), at time t T and at temperature T T The steel is tempered once or more times, during which secondary hardening effects occur in the treated steel until precipitation strengthening effects by alloying carbides are achieved.
[0019] As a result of the above treatment, a structure consisting of a mixture of bainitic ferrite, tempered martensite, retained austenite and carbides can be obtained.
[0020] Preferably, the tempering step (T) is carried out during a surface engineering process such as nitriding or physical vapor deposition (PVD). PVD processes produce coatings with properties compatible with the intended use of the steel. These can be protective, metallized or even decorative coatings.
[0021] It is also preferred to carry out a carbon partitioning step (P) instead of the tempering step (T).
[0022] Preferably, if in the first tempering, the tempering temperature T T At 400℃≤T T ≤600℃, and the tempering time t T In 1h≤t T Within the range of ≤3h.
[0023] When martensitic transformation occurs during cooling after the last tempering, it is preferred that the temperature be set at T T An additional tempering step is performed at ≤400°C to reduce the embrittlement of the newly formed martensite.
[0024] The process according to the invention is characterized by the fact that in step (A) at a temperature T A and austenitizing time t A , and obtain Ms(γ)≤340℃.
[0025] The method is characterized by the fact that the partial bainitization step (B) is terminated by means of one or more isothermal stops or by heating at 350°C ≥ T B ≥Ms(γ)+10℃ continuous cooling is carried out, where the temperature T BLower than the bainite transformation start temperature Bs of the steel and at least 10°C higher than the temperature Ms(γ), where T B ≥200℃.
[0026] After BQT treatment by the method according to the invention, at least 10% by volume of retained austenite is present in the final microstructure of the steel.
[0027] The method according to the invention is also characterized by the fact that the treated steel contains alloying additions (in % by weight): 0.4% - 2.3% C; 0.4% - 2.5% Mn; 0.5% - 3.0% Si; at least one of the following carbide formers: up to 17.0% Cr, up to 10.0% Mo, up to 4.0% V, while maintaining the following relationship: (% Si + % Al) ≥ 0.8%; and optional additives from the following group: up to 18.0% W, up to 0.2% Ti, up to 0.1% Nb, up to 2.0% Al, up to 4.5% Ni, up to 10.0% Co, up to 1.2% Cu, the remainder being iron and traces of unavoidable admixtures.
[0028] Furthermore, the invention relates to the use of the method according to the invention for producing tools and parts of machines and plants which work under harsh operating conditions, such as industrial knives, coin punches, plastic stamping dies.
[0029] The heat treatment method according to the present invention is used to form the alloying properties of the starting material, which is a medium carbon steel and a high carbon steel undergoing bainite transformation, wherein the chemical composition should ensure that the martensitic transformation start temperature Ms in the steel is ≤340°C. The chemical composition of the treated steel should be in the following range (in weight %): 0.4%-2.3% C; 0.4%-2.5% Mn; 0.5%-3.0% Si; at least one of the following carbide forming elements: up to 17.0% Cr, up to 10.0% Mo, up to 4.0% V, while maintaining the following relationship: (% Si + % Al) ≥ 0.8%; and optional additives from the following group: up to 18.0% W, up to 0.2% Ti, up to 0.1% Nb, up to 2.0% Al, up to 4.5% Ni, up to 10.0% Co, up to 1.2% Cu. The remaining components are iron and trace amounts of unavoidable admixtures.
[0030] The addition of silicon and / or aluminum is used here to suppress the precipitation process during the isothermal holding (B), allowing the formation of carbide-free ferrite during austempering, and better control of the carbide morphology during tempering. Due to the suppression of the precipitation process during the bainite transformation, carbon diffuses from the bainitic ferrite into the surrounding austenite instead of forming carbides. Increasing the carbon content of the austenite increases its thermal stability and allows it to remain in the microstructure in the form of a thin layer between the plates of bainitic ferrite. Replacing carbides with residual austenite in the form of a thin layer significantly improves the fracture resistance of the steel. Elements such as chromium, molybdenum, niobium and vanadium have the greatest impact on the secondary hardness achieved during tempering due to their tendency to form alloyed carbides. Due to the ability to machine parts with larger sizes, additives that increase hardenability, such as nickel and manganese, are also desirable. The alloy may also include alloying additives that form high melting point carbides or carbonitrides. Their presence reduces the grain size of the primary austenite, increases the number of nucleation sites for bainitic ferrite and causes structural homogenization, which has a beneficial effect on the properties of the alloy steel.
[0031] The content of impurities such as phosphorus, sulfur, oxygen, tin, and lead should be reduced to reduce their segregation within the boundaries and avoid intergranular embrittlement and temper embrittlement during heat treatment.
[0032] The purpose of the first step, austenitization (A), is to transform the initial structure of the steel into austenite or austenite with primary carbides. By choosing an appropriate temperature (T A ) and time (t A ), the chemical composition of austenite can be controlled, thereby controlling the dissolution process of alloying carbides. Increasing the alloying of austenite causes the region where phase transformation occurs to shift to longer times and lower temperatures. On the other hand, the presence of uniformly distributed, finely dispersed primary carbides can positively affect the strengthening of the steel, and also affect the morphology and transformation kinetics of the phase components, providing additional phase nucleation sites. Therefore, the parameters of the subsequent BQT treatment step are largely determined by the austenitizing conditions. Due to the risk of decarburization and / or oxidation caused by the high temperatures of this operation, it is recommended to carry out austenitizing in a vacuum furnace or under a protective atmosphere.
[0033] The purpose of the second step, austempering (B), is to produce a certain volume fraction of carbide-free bainite in the steel, in the form of bundles of nano- or submicron plates of bainitic ferrite separated by thin layers of residual austenite. Nano- or submicron carbide-free bainite is characterized by a favorable combination of high strength, fracture resistance and fatigue resistance. The purpose of the formation of bainite bundles is also to divide the primary austenite grains into smaller areas of so-called blocks, where partial martensitic transformation will occur in the next processing step (Q). The division of the primary austenite grains into smaller areas leads to significant fragmentation of the martensite formed therein. The fragmentation of the martensite increases the strength and plasticity of the microstructure. This step involves cooling the steel from the austenitizing temperature to the isothermal annealing temperature at a rate above the critical rate in order to avoid areas of diffuse ferrite and / or pearlite transformation. The temperature (T) at which the steel stops within the bainite range is 100°C. B ) and time (t B ) should be chosen experimentally according to the austenite chemical composition obtained, but it is preferred to use a bainite transformation T B This step is carried out in a relatively low temperature range of ≤320°C. Due to the low austempering temperature, a fine grain structure with bainite plates of submicron thickness and in some cases even of the order of tens of nanometers can be produced. Adequate fragmentation of the bainite structure leads to strengthening of the material, resulting in an increase in hardness and ultimate strength without a decrease in ductility. It should also be remembered that T B The temperature should be at least 10°C higher than the Ms(γ) temperature, since the Ms temperature is the average temperature for a given alloy and can locally take higher values. B The temperature should be selected to avoid premature occurrence of martensitic transformation. In addition, too low isothermal stopping temperature leads to slow transformation kinetics, which significantly increases the processing time, so it is preferred that T B ≥200℃. Using an isothermal stop above the Ms temperature further reduces the quenching deformation of the workpiece. As the bainite transformation proceeds, the austenite is enriched with carbon and therefore its thermal stability increases, which is particularly manifested in Ms (γ r ) temperature. Therefore, it is important to control the progress of the bainitization step so that it effectively affects the microstructure and properties of the steel and so that the temperature Ms (γ r ) is not reduced too much, which would prevent the next step of martensite quenching.
[0034] The purpose of the third step, quenching (Q), is to produce martensite in the steel structure in the form of very fine plates, laths or needles. This step consists in cooling the steel to the martensite transformation start temperature M of the remaining austenite in the material in the form of blocks. s (γ r ) and the martensitic transformation end temperature M f(γr). Martensite as a hard phase increases the hardness and wear resistance of the steel during machining. T Q The regulation of the temperature makes it possible to control the content of retained austenite and martensite, since with undercooling in the microstructure the fraction of martensite increases, while the fraction of austenite decreases. The phase composition of the steel can be determined according to the application of the workpiece, although it is recommended that at least 10% by volume of retained austenite remain in the steel. Holding time t Q depends on the cooling medium and the size of the charge and should be selected to allow the temperature T to be reached throughout the workpiece Q .
[0035] The fourth step, tempering (T), is crucial for the properties of the steel obtained as a result of the heat treatment according to the invention. It consists in annealing the charge once or more at a temperature at which the precipitation process and the diffusion of carbon from martensite to austenite occur simultaneously, so that embrittlement is reduced and the austenite increases its thermal stability. Due to the precipitation process during tempering, the steel is strengthened due to the uniform precipitation of finely dispersed carbides from the matrix. The effect of this phenomenon is an increase in the hardness of the workpiece, which is called secondary hardness. The finely dispersed alloy carbides combined with the matrix effectively contribute to increasing the mechanical parameters and functional parameters of the steel. In addition, in the case of high-carbon steels in which the content of residual austenite remaining after the bainitizing step and the quenching step is too high, the precipitation of carbides can lead to the instability of austenite and cause its partial martensitic transformation during cooling to room temperature, resulting in a reduction in the volume fraction of this soft phase. Additional tempering operations are then required to eliminate the embrittlement of the fresh martensite. The time, temperature and number of tempering steps should be selected individually for the workpiece, because the tempering step provides a wide range of possibilities for controlling the final properties of the steel. Typically, the tempering temperature is in the range of 400°C-750°C, preferably in the range of 400°C-600°C, and the time of a single section should not exceed 3 hours.
[0036] The content of retained austenite in the final microstructure of the steel is crucial to the properties obtained - retained austenite is a plastic phase and, in the appropriate amount and morphology, can significantly increase the impact strength, ductility and resistance to brittle fracture of the steel. At the same time, austenite supersaturated with carbon in the form of thin films and fine grains can experience the TRIP (transformation induced plasticity) effect, increasing strength and wear resistance. However, the stabilization of excessive austenite during tempering can lead to unsatisfactory hardness values and wear resistance, while the instability of too much austenite, especially when the martensitic transformation occurs after the last step of tempering, will lead to embrittlement of the workpiece. The tempering parameters also directly affect the precipitation and growth of carbides, which also affect the final properties of the steel. Excessive temperatures or excessive times of this treatment step can lead to excessive decarburization of martensite and bainitic ferrite, which translates into a reduction in the hardness of the material. At the same time, condensation of precipitates will occur, leading to reduced strengthening of the steel and a further reduction in hardness. Inappropriately selected tempering parameters can also lead to the growth of carbides at the grain boundaries and the formation of so-called carbide networks, significantly deteriorating the steel's resistance to brittle fracture. It is also important to bear in mind the known embrittlement effects of tempering of the first and second kind, which can occur during the tempering process. Properly conducting the tempering process gives the possibility to control the content and morphology of secondary carbides and the fraction of retained austenite, allowing to achieve high hardness values and wear resistance as well as increased impact strength and fracture resistance.
[0037] The heat treatment method for medium and high carbon alloy steels with high silicon content and / or aluminum content and carbide-forming alloying elements according to the present invention makes it possible to produce a very fine multiphase microstructure consisting of carbide-free bainite, tempered martensite, retained austenite and carbides. This new type of microstructure allows high hardness, strength, wear resistance to be combined with ductility and fracture resistance. This is possible by combining the mechanisms of precipitation strengthening of carbides, strengthening of hard martensite and bainitic ferrite phases and grain boundary strengthening. Grain boundary strengthening is the result of the high degree of crushing of phase components to submicron size and even nanometer size. On the other hand, adding sufficient amounts of silicon and / or aluminum inhibits the precipitation of cementite, particularly in bainite, making it more resistant to fracture. In turn, the presence of retained austenite in the form of thin layers and finely dispersed grains that exhibit percolation due to their content being more than 10% by volume is the reason for the increase in plasticity. In addition, the presence of undissolved carbides during austenitization can lead to the formation of bainite with a star-shaped morphology (acicular type) during the partial bainitization step. This type of structure is characterized by a large disorientation of the bainitic ferrite plates nucleated on the carbide precipitates, further increasing the fracture resistance of the steel.
[0038] The steel according to the invention has a different microstructure and chemical composition than the materials disclosed in the prior art. To date, no heat treatment method has been reported that simultaneously exploits all present strengthening mechanisms in tool steels, resulting in unique mechanical and functional properties. The method according to the invention makes it possible to control the phase fractions and morphology of the microstructure, allowing to achieve the desired properties of the steel in terms of its application and the requirements placed on tools and structural components. The parameters of each heat treatment step can be determined by calculations, computer simulations and experimental tests using a dilatometer.
[0039] The method according to the present invention, represented by the abbreviation BQT, can be used to form properties that require parts with higher impact strength and fracture resistance compared to conventional martensitic quenching and tempering treatments, while maintaining comparable hardness and strength. These parts can include industrial knives, coin punches and plastic stamping dies, among others. This treatment allows longer life of the parts and increases the trouble-free life of the equipment.
[0040] When the use conditions of the workpieces require steels with even higher fracture resistance and ductility than BQT-treated steels, at the expense of lower hardness, a modified BQT treatment process, the so-called BQP process, should be used. In the BQP treatment, a carbon partitioning (P) step is used instead of the tempering (T) step. During the partitioning step (P), carbon diffuses from the martensite and bainitic ferrite into the austenite, increasing its thermal and mechanical stability. During the partitioning step (P), in contrast to the tempering step (T), there is no carbide precipitation and no secondary hardness effects. The treatment of BQP is the subject of further work.
[0041] The presented embodiments of the invention are merely illustrative and in no way limitative of the claimed invention.
[0042] Example 1
[0043] Samples made of K360 steel with the chemical composition shown in Table 1 were subjected to a BQT type treatment. This steel is characterized by high concentrations of carbide formers, namely Cr, Mo, V, Nb, W, and an increased silicon and aluminum content (% Si + % Al) = 1.74% by weight, at which there is an inhibition of the precipitation process during the austempering step. The chemical composition of the steel meets the requirements for a material of this type of treatment.
[0044] Table 1 Chemical composition of K360 steel, in % by weight.
[0045]
[0046] T A =1050℃ and t A= 15 min was used as the parameter for the austenitizing step, which allowed partial dissolution of the carbides. As a result, M7C3, M 23 Carbides of type C6 and M2C, whose volume fraction does not exceed 10% by volume, are homogeneously distributed in the matrix, while alloying of austenite is sufficient for the application of the developed technology. Based on expansion studies, the martensitic transformation start temperature Ms(γ)=240°C was determined.
[0047] Isothermal quenching at T B =260℃, T B =260°C is 20°C higher than Ms(γ). Cooling to isothermal stop is carried out in hot oil, which allows cooling rates above the critical cooling rate. Expansion studies show that the completion of isothermal transformation at this temperature occurs after 16h30min. Based on the expansion curve showing the kinetics of bainite transformation, the stop durations leading to 20% and 60% progress of bainite transformation are determined. They are t B20% =2h 3min and t B60% =3h 33min.
[0048] As a result of the formation of bainitic ferrite during austempering, the martensitic transformation start temperatures of the remaining austenite drop to Ms(γ20%)=210°C and Ms(γ40%)=190°C, respectively, while the end temperatures Ms(γ20%)=210°C and Ms(γ40%)=190°C, respectively. f (γ r ) was recorded as below room temperature. For both series of samples, the quenching temperature was determined as T Q =30℃. According to the patent principle, T Q In M s (γ r ) and M f (γ r ) temperature range. Q The time is assumed to be 10 minutes.
[0049] According to experimental research and material safety data sheets, the tempering temperature and tempering time are determined: T P =500℃,t p = 2h. These parameters allow to observe the influence of secondary hardness in the steel. Only one tempering section was used, since no martensitic transformation was observed during cooling and therefore tempering did not destabilize the retained austenite. In both series of samples, the fraction of retained austenite was estimated to be about 15% by volume.
[0050] The obtained mechanical properties of the samples are compared with those of the steel after conventional treatment (QT), i.e. martensitic quenching combined with 3 temperings at 500°C for 2h, and after a simple austempering treatment at 260°C for 16h 30min. The values are summarized in Table 2.
[0051] Table 2
[0052] Examples of selected mechanical properties of BQT treated K360 steel using different processing parameters
[0053]
[0054]
[0055] The strength parameters and hardness of the samples after the BQT treatment are similar to the values obtained for steels subjected to conventional toughening, while the impact strength of the steels is higher after the application of the technology that is the subject of the present invention. Particularly high compressive strengths are shown for the samples after the application of a section of 60% advanced bainitic transformation. Complete bainitization of the steel significantly improves its ductility, but hardness and strength reach very low values.
[0056] Example 2
[0057] Samples made of K340 steel were subjected to BQT treatment. This steel is characterized by a high total content of silicon and aluminum, which allows slowing down the cementite precipitation process, and a large amount of other carbide-forming additives, in particular chromium and molybdenum, as listed in Table 3.
[0058] Table 3 Chemical composition of K340 steel
[0059]
[0060] Based on the expansion test, the austenitizing temperature T is determined A =1050℃ and time t A = 15min. After such austenitizing parameters, the martensite transformation start temperature Ms(γ) = 245°C. Isothermal quenching at T B =270℃, T B = 270°C is about 25°C higher than the Ms(γ) temperature. The austempering time is selected so as to achieve 60% progression of the bainite transformation, which translates into the presence of about 30% bainitic ferrite in the structure, and the austempering time is t B =1h 26min. After this time, the retained austenite-martensite transformation temperature Ms(γr)=115°C is obtained.
[0061] The tempering parameters were selected based on the expansion study. It was decided to temper three times, with the first tempering temperature being T T1 =550℃, continuous t T =2h, and the next two tempering temperatures are T T2.3=450°C for 2h. The first higher temperature allows the residual austenite γr to be unstable, resulting in carbide release and martensitic transformation during cooling to room temperature, where after tempering, the martensitic transformation start temperature Ms(γT1) is 120°C. The next two tempering steps performed at lower temperatures allow martensite relaxation and further carbide precipitation while retaining some austenite, thereby increasing the fracture resistance of the steel. The proposed treatment is compared with samples after the conventional process of quenching at 550°C and three temperings. The results are shown in Table 4.
[0062] Table 4
[0063] Properties of K340 steel after different treatments
[0064] deal with HRC hardness Impact strength KV[J] Quenching and tempering 59.2±1.3 1±0.1 QUR 58.6±1.4 1.4±0.1
[0065] After the proposed treatment, the hardness decreased slightly, but still within the error range. At the same time, a 40% increase in the impact strength of the sample could be observed.
[0066] Example 3
[0067] Samples made of WCL steel having the chemical composition shown in Table 5 were subjected to a BQT type treatment.
[0068] Table 5 Chemical composition of WCL steel, in % by weight.
[0069]
[0070] T A =1050℃ and t A =15min was used as the austenitization parameter. Based on the expansion heat treatment curve of martensite quenching, the martensite transformation start temperature Ms(γ)≈310℃ was determined.
[0071] Isothermal quenching at T B =320 ° C. The expansion studies showed that at this temperature the completion of the bainite transformation occurs after about 12 h. From the expansion curves showing the kinetics of the bainite transformation, the stop durations leading to 20%, 40% and 60% of the progress of the bainite transformation were determined. They are t B20% =33min, t B40% =56min and t B60% =74min.
[0072] The step (Q) carried out after the partial bainite transformation was carried out in water at 25°C. Three repetitions of the method were carried out, differing in the tempering step (T). The step was carried out at 450°C, 500°C, 550°C and the tempering time for each method was 2h.
[0073] Exemplary values of hardness and austenite content are shown in Table 6.
[0074] Table 6
[0075] Hardness and retained austenite content of WCL steel after BQT process
[0076]
[0077]
Claims
1. A method for heat treatment of medium carbon alloy steel and high carbon alloy steel undergoing bainite transformation, comprising heating, cooling and tempering the steel, characterized in that: The method comprises the following subsequent steps: (A) Heating the steel to the austenitizing temperature T A >A c1k And keep it at this temperature for a duration of t A ; (B) cooling the steel that has undergone the bainite transformation to an isothermal annealing temperature T B , where 350℃≥T B ≥Ms(γ)+10℃, and keep at this temperature for a period of time t B , until a volume fraction of 10%-70% bainitic ferrite is produced; (Q) Cooling the steel to a temperature T Q , the temperature T Q The martensitic transformation start temperature M of the retained austenite remaining after partial bainitization (step B) is s (γ r ) and the martensitic transformation end temperature M f (γ r ) and keep the value for duration t Q , until the temperature is uniform throughout the piece; (T) at time t T and temperature T T The steel is tempered once or more times, with secondary hardening effects in the treated steel, until precipitation strengthening by alloying carbides is achieved.
2. The method according to claim 1, characterized in that: The tempering step (T) is performed, for example, during a surface engineering process such as nitridation or physical vapor deposition.
3. The method according to claim 1, characterized in that A carbon partitioning step (P) is performed instead of the tempering step (T).
4. The method according to claim 1, characterized in that In the first tempering, the tempering temperature T T At 400℃≤T T ≤600℃, and the tempering time t T In 1h≤t T Within the range of ≤3h.
5. The method according to claim 1, characterized in that When martensitic transformation occurs during cooling after the last tempering, at T T An additional tempering step is performed at ≤400°C to reduce the embrittlement of the newly formed martensite.
6. The method according to claim 1, characterized in that In step (A), at temperature T A and austenitizing time t A , and obtain Ms(γ)≤340℃.
7. The method according to claim 1, characterized in that The partial bainitization step (B) is carried out by one or more isothermal stops or by heating at 350°C ≥ T B ≥Ms(γ)+10℃ continuous cooling, where T B The temperature is lower than the bainite transformation start temperature Bs of the steel and higher than the temperature Ms(γ) by at least 10°C, wherein T B ≥200℃.
8. The method according to claim 1, characterized in that After the BQT treatment, there is at least 10% by volume of retained austenite in the final microstructure of the steel.
9. The method according to claim 1, characterized in that: The treated steel comprises alloying additives (in wt%): 0.4%-2.3% C; 0.4%-2.5% Mn; 0.5%-3.0% Si; at least one of the following carbide-forming elements: up to 17.0% Cr, up to 10.0% Mo, up to 4.0% V, while maintaining the following relationship: (% Si + % Al) ≥ 0.8%; and optional additives from the following group: W up to 18.0%, Ti up to 0.2%, Nb up to 0.1%, Al up to 2.0%, Ni up to 4.5%, Co up to 10.0%, Cu up to 1.2%, the remainder being iron and trace amounts of unavoidable admixtures.
10. Use of the method according to claims 1 to 9 for producing tools and parts of machines and plants operating under harsh operating conditions, such as industrial knives, coin punches, plastic stamping dies.
Citation Information
Patent Citations
Upper bainite quenching strengthening technology for heat treatment of chromium-manganese-silicon low-alloy structural steel
CN101724736A
Heat treatment technology for light drilling tool material
CN102828011A
Method for improving impact toughness of tempered low-alloy granular bainite steel
CN109207693A
Heat treatment method capable of realizing both precipitation strengthening and lower bainite phase-transformation strengthening
CN111876569A
Bainite steel and methods of manufacture thereof
EP2410070A1